1997
DOI: 10.1086/514504
|View full text |Cite
|
Sign up to set email alerts
|

International Conference for the Development of a Consensus on the Management and Prevention of Severe Candidal Infections

Abstract: Because of the rapidly increasing incidence of serious candidal infections, a consensus conference of 22 investigators from the United States, Europe, and Japan was held to discuss strategies for the prevention and treatment of deep-organ infections caused by Candida species. Commonly asked questions concerning the management of candidal infections were selected for discussion by the participating investigators. Possible answers to the questions were developed by the investigators, who then voted anonymously f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
255
0
20

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(277 citation statements)
references
References 2 publications
2
255
0
20
Order By: Relevance
“…Nontoxic systemic serum levels of 50-100 mg ml À1 are achievable with oral administration of 100-200 mg kg À1 per day in four divided doses. 40 Our findings, of effective cell killing with tolerable equivalent human doses of 5-FC suggest significant advantages in using MVA-mediated transfer of FCU1 for molecular therapy since in previous investigations involving 5-FC/CDase a dose of at least 500 mg kg À1 5-FC was required for therapeutic effects in tumor-bearing animals. [2][3][4][5][6][7][34][35][36]41 Attempts to reduce the dose of 5-FC to less than 500 mg kg À1 resulted in no effect on tumor growth.…”
Section: Discussionmentioning
confidence: 63%
“…Nontoxic systemic serum levels of 50-100 mg ml À1 are achievable with oral administration of 100-200 mg kg À1 per day in four divided doses. 40 Our findings, of effective cell killing with tolerable equivalent human doses of 5-FC suggest significant advantages in using MVA-mediated transfer of FCU1 for molecular therapy since in previous investigations involving 5-FC/CDase a dose of at least 500 mg kg À1 5-FC was required for therapeutic effects in tumor-bearing animals. [2][3][4][5][6][7][34][35][36]41 Attempts to reduce the dose of 5-FC to less than 500 mg kg À1 resulted in no effect on tumor growth.…”
Section: Discussionmentioning
confidence: 63%
“…A strong consensus has recently emerged on the notion that intravenous lines should be withdrawn from candidemic patients whenever feasible. 18 Failure to effect complete exchange was strongly associated with the persistence of candidemia in a study by Rex et al 19 More recently, a prospective multicenter study from a tertiary care hospital in Brazil demonstrated that non-removal of the central venous catheter, in addition to older age, were the only factors associated with an increased risk of death. 20 As in this study, we found that retaining the catheter was associated with poor outcome.…”
Section: Discussionmentioning
confidence: 96%
“…Suggested measures for management of central or peripheral intravenous catheters are still controversial. 9,16,32 Strategies such as decreasing the number of antibiotics described and initiating azole chemotherapy for a high-risk group 18 have been suggested but have not been widely implemented. The role of azole chemoprophylaxis in the development of drug resistance in C. albicans and in emergence of less susceptible fungal pathogens needs to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Severe mucositis is considered to be a risk factor for superficial as well as invasive yeast infections. 54 Almost all cases of systemic candidiasis originate from the oral cavity. 38 Candida albicans is encountered most frequently, but other species are seen in addition, eg C. tropicalis, C. krusei, C. parapsilosis, C. glabrata, Mucor, and Aspergillus spp.…”
Section: Pathophysiologymentioning
confidence: 99%